Synthesis and biological evaluation of novel bi-gold mitocans in lung cancer cells - Ding, Wenwen; Cui, Qingbin; Lu, Wenhua; Du, Yongliang; Luo, Yao; Hu, Yumin; Huang, Peng; Wen, Shijun (Frontiers in Chemistry, 2023)
Mitochondria are promising drug target for cancer treatment. We previously demonstrated that a bi-gold compound BGC2a was more potent than the mono-gold drug auranofin in suppressing cancer cells due to increased gold atom number that led to higher drug accumulation in and thereby inhibition of mitochondria. To exploit the potential of this new strategy, we further designed and synthesized a series of bi-gold mitocans, the compounds targeting mitochondria. The results showed that most of the newly synthesized mitocans exhibited obviously lower IC50 than auranofin, an old drug that is repurposed in clinical trials for cancer treatment. The best mitocan C3P4 was nearly 2-fold more potent than BGC2a in human non-small cell lung cancer A549 cells and mantle cell lymphoma Jeko-1 cells, exhibiting substantial colony formation-suppressing and tumor-suppressing effects in A549 cells xenograft model. C3P4 induced apoptosis in a dose-dependent manner and arrested cell cycle at G0/G1 phase. The mechanistic study showed that C3P4 significantly increased the global reactive oxygen species and mitochondrial superoxide level, and reduced the mitochondrial membrane potential. C3P4 preferentially accumulated in mitochondria as measured by the gold content and substantially inhibited oxygen consumption rate and ATP production. These results further validated our hypothesis that targeting mitochondria would be promising to develop more potent anticancer agents. C3P4 may be further evaluated as a drug candidate for lung cancer treatment.